Measles among migrants in the European Union and the European Economic Area. Issue 1 (February 2016) - Williams, Gemma A.; Bacci, Sabrina; Shadwick, Rebecca; Tillmann, Taavi; Rechel, Bernd; Noori, Teymur; Suk, Jonathan E.; Odone, Anna; Ingleby, Jonathan D.; Mladovsky, Philipa; Mckee, Martin
Aims: Progress towards meeting the goal of measles elimination in the EU and the European Economic Area (EEA) by 2015 is being obstructed, as some children are either not immunized on time or never immunized. One group thought to be at increased risk of measles is migrants; however, the extent to which this is the case is poorly understood, due to a lack of data. This paper addresses this evidence gap by providing an overview of the burden of measles in migrant populations in the EU/EEA.Methods: Data were collected through a comprehensive literature review, a country survey of EU/EEA member states and information from measles experts gathered at an infectious disease workshop.Results: Our results showed incomplete data on measles in migrant populations, as national surveillance systems do not systematically record migration-specific information; however, evidence from the literature review and country survey suggested that some measles outbreaks in the EU/EEA were due to sub-optimal vaccination coverage in migrant populations. Conclusions : We conclude that it is essential that routine surveillance of measles cases and measles, mumps and rubella (MMR) vaccination coverage become strengthened, to capture migrant-specific data. These data can help to inform the provision of preventive services, which may need to reach out to vulnerable migrant populations that currently face barriers in accessing routine immunization and health services.